Stability of a parametrically - excited system under two excitations - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 1993)
In this paper, the stability of a parametrically - excited system under two excitations of different orders is studied. It is found that these excitations either enforce their actions or eliminate each other. Hence, the unstable region can be either expanded or restricted.